Crossmodal identification. - Calvert, G; Brammer, M; Iversen, S (1998)
Everyday experience involves the continuous integration of information from multiple sensory inputs. Such crossmodal interactions are advantageous since the combined action of different sensory cues can provide information unavailable from their individual operation, reducing perceptual ambiguity and enhancing responsiveness. The behavioural consequences of such multimodal processes and their putative neural mechanisms have been investigated extensively with respect to orienting behaviour and, to a lesser extent, the crossmodal coordination of spatial attention. These operations are concerned mainly with the determination of stimulus location. However, information from different sensory streams can also be combined to assist stimulus identification. Psychophysical and physiological data indicate that these two crossmodal processes are subject to different temporal and spatial constraints both at the behavioural and neuronal level and involve the participation of distinct neural substrates. Here we review the evidence for such a dissociation and discuss recent neurophysiological, neuroanatomical and neuroimaging findings that shed light on the mechanisms underlying crossmodal identification, with specific reference to audio-visual speech perception.